INOVASI TAKOYAKI ISIAN BANDENG SUWIR DENGAN SUBSTITUSI TEPUNG SINGKONG DAN PENAMBAHAN TEPUNG TEMPE - Narulita, Vidia; Niken Purwidiani; Lilis Sulandar; Ila Huda Puspita Dewi (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to find out the best formulation with sensory quality results which include shape, color, aroma, texture, and taste as well as nutritional content from the results of proximate tests (protein, carbohydrates, fat, water and fiber) of shredded milkfish stuffed takoyaki with cassava flour substitution and the addition of tempeh flour. Sensory tests were conducted on 30 panelists to assess criteria for shape, color (outer and inside), aroma, texture, taste, and overall likability. The collected data was then tested using a single anova test and a duncan follow-up test. The results showed that takoyaki with a proportion of 90% wheat flour and 10% cassava flour was the best formula based on sensory quality test scores that produced takoyaki with a round shape, quite brown on the outside with a yellowish creamy inner color, very distinctive takoyaki flavor, soft texture, and quite savory taste. The results of the proximate test produced takoyaki with a protein content of 9.51%, carbohydrates 51.70%, fat 6.08%, water 29.80%, and fiber 2.01%.